EDUKASI EVAKUASI BENCANA KEBAKARAN PADA PENGELOLALHAN GEDUNG GRAHA RS ISLAM SURABAYA - budhi setianto; Akas Yekti Pulih Asih; Agus Aan Adriansyah; Difran Nobel Bistara (Politeknik Negeri Sriwijaya, 2021)
Fires can occur anywhere and anytime; fire management needs to be understood for residents of high-rise buildings so that when a fire occurs, there are no casualties. Every team member who works in a hospital must know about fire disaster management, and the last training exercise was in August 2014 at the time of the first accreditation. Understanding fire management is very much needed, especially in carrying out fire disaster evacuations. The Surabaya Islamic Hospital has a 5-story house building used to provide health services. Every worker who occupies the facility is required to attend fire evacuation training. As many as 88 employees have held training for fire disaster evacuation, and participants take theory and practice classes. participants are very enthusiastic about participating in the training Providing disaster evacuation education is needed by every team member as a condition for implementing Hospital Accreditation; there is an increase in abilities and skills in terms of theory or practice related to fire disaster management.